Technical Note: Relationships between gamma criteria and action levels: Results of a multicenter audit of gamma agreement index results. Issue 3 (25th February 2016) - Crowe, Scott B.; Sutherland, Bess; Wilks, Rachael; Seshadri, Venkatakrishnan; Sylvander, Steven; Trapp, Jamie V.; Kairn, Tanya
Abstract : Purpose: The aim of this work was to use a multicenter audit of modulated radiotherapy quality assurance (QA) data to provide a practical examination of gamma evaluation criteria and action level selection. The use of the gamma evaluation method for patient‐specific pretreatment QA is widespread, with most commercial solutions implementing the method. Methods: Gamma agreement indices were calculated using the criteria 1%/1 mm, 2%/2 mm, 2%/3 mm, 3%/2 mm, 3%/3 mm, and 5%/3 mm for 1265 pretreatment QA measurements, planned at seven treatment centers, using four different treatment planning systems, delivered using three different delivery systems (intensity‐modulated radiation therapy, volumetric‐modulated arc therapy, and helical tomotherapy) and measured using three different dose measurement systems. The sensitivity of each pair of gamma criteria was evaluated relative to the gamma agreement indices calculated using 3%/3 mm. Results: A linear relationship was observed for 2%/2 mm, 2%/3 mm, and 3%/2 mm. This result implies that most beams failing at 3%/3 mm would also fail for those criteria, if the action level was adjusted appropriately. Some borderline plans might be passed or failed depending on the relative priority (tighter tolerance) used for dose difference or distance to agreement evaluation. Dosimeter resolution and treatment modality were found to have a smaller effect on the results of QA measurements than the number of dimensions (2D or 3D) over which the gamma evaluation was calculated. Conclusions: This work provides a method (and a large sample of results) for calculating equivalent action levels for different gamma evaluation criteria. This work constitutes a valuable guide for clinical decision making and a means to compare published gamma evaluation results from studies using different evaluation criteria. More generally, the data provided by this work support the recommendation that gamma criteria that specifically prioritize the property of greatest clinical importance for each treatment modality of anatomical site should be selected when using gamma evaluations for modulated radiotherapy QA. It is therefore suggested that departments using the gamma evaluation as a QA analysis tool should consider the relative importance of dose difference and distance to agreement, when selecting gamma evaluation criteria.